Human Placenta-Derived Mesenchymal Stem Cells Ameliorate Diabetic Neuropathy via Wnt Signaling Pathway - Songsong Pan; Sushant S. Hada; Yang Liu; Chao Hu; Mengdie Zhou; Shaoqiu Zheng; Minjie Xu; Changsheng Shi; Shiwu Yin; Xiaoyun Xie (Stem Cells International)
Objectives. To investigate the effect of placenta-derived mesenchymal stem cells (PMSCs) on diabetic peripheral neuropathy and explore the role of Wnt signaling pathway. Method. Twenty-seven male db/db mice were randomly categorized into the control group, PMSC group, and PMSC treatment with Wnt inhibitor treatment group. Intervention was initiated in week 22. Thermal stimulation response was determined with a plantar analgesia tester. The mice were sacrificed on 7, 14, and 28 days. The morphology of sciatic nerves was observed by electron microscopy, and the expression of protein gene product (PGP) 9.5, S100β, and Ku80 was detected by immunofluorescence. Bax, β-catenin, and dishevelled1 (DVL1) were detected by western blot. Results. Thermal stimulation response was improved in the PMSC group on 14 and 28 days. Compared with the control group, PGP9.5 was increased in the PMSC group, accompanied by a significant increase in the expression of S100β. On the contrary, LGK974 inhibited the effect of PMSCs on thermal stimulation response and the expression of PGP9.5 and S100β. Both PGP9.5 and S100β were correlated with Ku80 in fluorescence colocalization. The myelin sheath of sciatic nerves in the PMSC group was uniform and dense compared with that in the control group. The effects of PMSCs promoting myelin repair were significantly inhibited in the PMSC+LGK974 group. Bax in the PMSC group expressed less than the control group. In contrast, the expressions of β-catenin and DVL1 were higher compared with that in the control group on the 14th and 28th days. The expression of DVL1 and β-catenin was lower in the PMSC+LGK974 group than in the PMSC group. Conclusions. PMSCs improved the symptoms of diabetic peripheral neuropathy, along with the improvement of nerve myelin lesions, promotion of nerve regeneration, and activation of Schwann cells, which might be related to the regulation of Wnt signaling pathway and inhibition of apoptosis.